Response of sugarcane ratoon to nitrogen without and with the application of silicon - Montes Nogueira Borges, Bernardo Melo [UNESP]; Firmato De Almeida, Thiago Batista [UNESP]; Prado, Renato De Mello [UNESP] (Taylor & Francis Inc, 2016)
The objective was to evaluate the effect of nitrogen, associated to silicon, on soil chemical properties, nutritional status and yield of the second sugarcane ratoon. The experiment was carried out at a Haplustox, loamy texture. The treatments consisted of urea rates of 0, 40, 80, 120 and 160kg ha(-1) and two sources of correctives: silicate and lime. The use of nitrogen (N) associated with silicate and lime did not affect soil fertility; however, the use of silicate increased soil silicon content at harvest. Growth variables were not affected by the application of the treatments, except stalk number at harvest, which increased in the presence of silicon. N rates and the correctives did not affect the crop nutritional status, but affected the N and Si accumulation in the plant. The N rates increased the sugarcane ratoon yield regardless the use of silicate; however, they did not affect its technological quality.
Keywords: Saccharum spp; fertilization; lime; silicate; sugarcane ratoon